Severe phenotypes of B3GAT3-related disorder caused by two heterozygous variants: a case report and literature review - Ying Li; Chuangwen Zhang; Hongyu Zhang; Weiqi Feng; Qiuji Wang; Ruixin Fan (BMC, 2022)
Abstract Background Linkeropathies refers to a series of extremely rare hereditary connective tissue diseases affected by various glycosyltransferases in the biosynthesis of proteoglycans. We report for the first time two heterozygous variants of B3GAT3 in a Chinese infant, in whom Marfan syndrome was suspected at birth. Case presentation A 2-month-old boy from a non-consanguineous Chinese family without a family history presented severe phenotypes of joint dislocation, obvious flexion contractures of the elbow, arachnodactyly with slightly adducted thumbs, cranial dysplasia, foot abnormalities and aortic root dilation; Marfan syndrome was suspected at birth. Our patient was the youngest, at the age of 2 months, to experience aortic root dilation. Two B3GAT3 variants, NM_012200.2, c.752T>C, p.V251A and c.47C>A, p.S16*, with heterozygosity were identified in the patient by whole-exome sequencing; the variants were inherited from his parents. During close follow-up, significant changes in the cranial profile and obvious external hydrocephalus were present at the age of 7 months, which differs from previously reported cases. Conclusion We diagnosed a patient with congenital heart defects at an early age with a B3GAT3-related disorder instead of Marfan syndrome and expanded the spectrum of B3GAT3-related disorders. We also provide a literature review of reported B3GAT3 cases; for at least one of the variants, this is the first report of genotype-phenotype correlations in individuals with cardiovascular defects being related to the acceptor substrate-binding subdomain of B3GAT3.